Testing the drug use and condomless anal sex link among sexual minority men: The predictive utility of marijuana and interactions with relationship status. (1st November 2020) - Starks, Tyrel J.; Jones, S. Scott; Kyre, Kory; Robles, Gabriel; Cain, Demetria; Jimenez, Ruben; Stephenson, Rob; Sullivan, Patrick S.
Highlights: Relationship status contextualized drug use and casual partner CAS associations. Marijuana increased odds of CAS for single and monogamous SMM. Club drugs increased CAS odds and frequency for single and non-monogamous SMM. Associations between marijuana and CAS were smaller than club drugs. Abstract: Background: The association between drug use and condomless anal sex (CAS) is well documented among sexual minority men (SMM). Less is known about whether this association generalizes to marijuana and across relationship status and sexual agreements groups (single, partnered monogamous, partnered open –outside partners permitted, and partnered monogamish –outside partners permitted when main partners are together). Methods: A nationwide sample of SMM ( N = 65, 707) were recruited through a geosocial networking app between November 2017 and November 2019. Participants reported on drug use and instances of CAS with casual partners in the previous 30 days. Results: Both marijuana and club drug use were associated with the occurrence of CAS with casual partners among single men. Only club drug use was associated with CAS frequency in this group. The association between marijuana and the occurrence of CAS did not differ significantly among monogamous men, while the associations between club drug use and the occurrence as well as frequency of CAS were significantly weaker. Meanwhile, the associations between club drug use and the occurrence as well as frequency of CAS did not differ significantly between single and non-monogamous (open and monogamish) subgroups; however, the association between marijuana and the occurrence of CAS was significantly weaker. Conclusions: Findings largely replicated the robust association between club drug use and CAS with casual partners. They support the assertion that marijuana use predicts sexual risk for some SMM subgroups. Finally, they illustrate the potential for relationship status – and sexual agreements – to contextualize associations between drug use and CAS.